Factors of Students Participating in Online Examination - Sugilar Sugilar (Journal of Education and Learning (EduLearn), 2016)
The purpose of the study is to discover determinant factors of students' participation in online examination based on expectancy-value theory. The method used was group comparison between the groups of participating and nonparticipating students. The results showed that the following factors differentiated the two groups, i.e.: (1) self efficacy in using computers (t=12.81, p less than 0.01), (2) perceived of easiness in operating an online examination (t=9.51, p less than 0.01), (3) perceived of the importance of online examination (t=5.58, t less than 0.01), (4) intrinsic value of online examination (t=10.58, p less than 001), and (5) cost of online examination (t=-2.05, p=0.029). In addition, the following students' personal factors were also compared and the results were (1) age (t=-2.01, p=0.46), (2) grade point average (t=-5.546, 0 less than 0.01), (3) sex (x2=28.51, p less than 0.01), and (4) marital status (x2=6.50, p=0.011). The results concluded that the expectancy and value theory was useful for explaining and predicting students' participation in online examinations.